UPAYA MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INDONESIA MENGGUNAKAN MEDIA DIGITAL IFP STORYTELLING TK NURUN NAJAH KAJARHARJO - Audina, Anisa Putri; Wijaya Adi Putra; Ratnasari Dwi Ade Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are a fundamental ability in early childhood language development, as they form the foundation for communication, social interaction, and readiness for learning at the next educational level. Initial observations at TK Nurun Najah Kajarharjo indicated that children’s Indonesian speaking skills had not developed optimally. The children tended to be passive, lacked self-confidence, had limited vocabulary, and experienced difficulties in expressing ideas and retelling stories coherently. This study employed a Classroom Action Research design conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants were 20 kindergarten students at TK Nurun Najah Kajarharjo. Data were collected through observation of speaking activities, performance-based assessments, and documentation. Data analysis was carried out using descriptive qualitative and quantitative approaches to examine changes in the learning process and improvements in children’s learning outcomes. The results showed that the implementation of IFP storytelling had a positive impact on the quality of learning and students’ speaking development. In Cycle I, children began to show interest and initial confidence in speaking; however, their utterances were still dominated by one- or two-word responses and relied heavily on teacher guidance. In Cycle II, after the learning activities were modified to be more interactive and child-centered, a significant improvement was observed. Quantitatively, most children reached the categories of developing as expected and very well developed. Qualitatively, the learning outcomes revealed improvements in children’s ability to construct simple sentences, increased fluency and clarity of pronunciation, expanded vocabulary, and more coherent retelling skills. The children also demonstrated greater initiative in speaking, increased confidence in performing, and improved quality of verbal interaction in the classroom. Therefore, it can be concluded that digital IFP storytelling is effective in enhancing young children’s Indonesian speaking skills while also improving the overall quality of the learning process.